Association of Tripartite Motif Containing 11 rs564309 With Tau Pathology in Progressive Supranuclear Palsy. Issue 5 (6th March 2020) - Valentino, Rebecca R.; Koga, Shunsuke; Heckman, Michael G.; Brushaber, Danielle E.; Diehl, Nancy N.; Walton, Ronald L.; Dickson, Dennis W.; Ross, Owen A.
Abstract: Background: Intronic variant rs564309 in tripartite motif containing 11 (TRIM11 ) is associated with clinical phenotypic differences in progressive supranuclear palsy (PSP), whereby the minor allele (A) is more common in atypical PSP than typical PSP (PSP‐Richardson's syndrome). However, rs564309 has not been investigated relative to neuropathological outcomes. Objective: Evaluate the association of rs564309 with the neuropathologically assessed severity of tau pathology, as measured by semi‐quantitative scores for neurofibrillary tangles, tufted astrocytes, neuropil threads, and oligodendroglial coiled bodies. Methods: 797 neuropathologically confirmed PSP cases were genotyped for TRIM11 rs564309 and assessed for tau pathology across 20 neuroanatomical regions. Tau pathology measures and age at death were examined for association with TRIM11 rs564309‐A using multivariable linear regression models. Results: TRIM11 rs564309‐A was associated with increased neurofibrillary tangles pathology ( P = 0.050), but was not significantly associated with age at death, neuropil threads, coiled bodies, or tufted astrocytes tau pathology scores. Conclusions: TRIM11 rs564309 may influence burden of neurofibrillary tangles tau pathology in PSP; further study is warranted. © 2020 International Parkinson and Movement Disorder Society